Ultrafast proton-assisted tunneling through ZrO2 in dye-sensitized SnO2-core/ZrO2-shell films. Issue 57 (2nd July 2018) - Swierk, John R.; McCool, Nicholas S.; Röhr, Jason A.; Hedström, Svante; Konezny, Steven J.; Nemes, Coleen T.; Xu, Pengtao; Batista, Victor S.; Mallouk, Thomas E.; Schmuttenmaer, Charles A.
Abstract : Exposing ZrO2 to strong acid induces protonic defects that permit ultrafast electron transfer through at least 4 nm of ZrO2 . Abstract : Core–shell architectures are used to modulate injection and recombination in dye-sensitized photoelectrochemical cells. Here, we demonstrate that exposing SnO2 -core/ZrO2 -shell films to acid permits photoinduced electron transfer through ZrO2 -shells at least 4 nm thick. A novel mechanism of charge transfer is proposed where protonic defects permit ultrafast trap-assisted tunneling of electrons.